Simulation and experimental investigation on the wavefront correction performance of a dual magnetic connection deformable mirror under high-power laser irradiation - Zheng, Yamin; Zhuang, Yongchen; Lin, Shibing; Wang, Deen; Zhang, Yifan; Huang, Lei (Frontiers in Physics, 2023)
Deformable mirrors (DMs) are widely used in high-power laser systems to improve the output beam quality. However, under high-power laser irradiation, the heat accumulates on the DM mirror surface and results in high-power laser induced distortions (LID), which will degrade the wavefront correction performance of the DM. In order to suppress the negative impact of the LID on the DM’s performance, we introduce the dual magnetic connection DM (DDM), in which the mirror and the base are connected by two-layer magnets. Configuration of the DDM is presented. The simulation is established to analyze the LID characteristics as well as the wavefront correction performance of the DDM. An experiment is established to investigate the LID of the DDM in practical conditions. Simulation and experiment results indicate that under high-power laser irradiation, the DDM could effectively suppress the LID and maintain good wavefront correction capability.